Cobalt Plasmonic Superstructures Enable Almost 100% Broadband Photon Efficient CO2 Photocatalysis. Issue 24 (10th May 2020) - Feng, Kai; Wang, Shenghua; Zhang, Dake; Wang, Lu; Yu, Yingying; Feng, Kun; Li, Zhao; Zhu, Zhijie; Li, Chaoran; Cai, Mujin; Wu, Zhiyi; Kong, Ning; et al.
Abstract: The efficiency of heterogeneous photocatalysis for converting solar to chemical energy is low on a per photon basis mainly because of the difficulty of capturing and utilizing light across the entire solar spectral wavelength range. This challenge is addressed herein with a plasmonic superstructure, fashioned as an array of nanoscale needles comprising cobalt nanocrystals assembled within a sheath of porous silica grown on a fluorine tin oxide substrate. This plasmonic superstructure can strongly absorb sunlight through different mechanisms including enhanced plasmonic excitation by the hybridization of Co nanoparticles in close proximity, as well as inter‐ and intra‐band transitions. With nearly 100% sunlight harvesting ability, it drives the photothermal hydrogenation of carbon dioxide with a 20‐fold rate increase from the silica‐supported cobalt catalyst. The present work bridges the gap between strong light‐absorbing plasmonic superstructures with photothermal CO2 catalysis toward the complete utilization of the solar energy. Abstract : A cobalt plasmonic superstructure is developed to enable almost 100% broadband photon efficient CO2 photocatalysis through enhanced plasmonic excitation by the hybridization of Co nanoparticles in close proximity, as well as inter‐ and intra‐band transitions. This work will bridge the gap between plasmonic absorbers with photothermal catalysis, toward the complete utilization of the solar energy.